2010
DOI: 10.1007/s10518-010-9227-1
|View full text |Cite
|
Sign up to set email alerts
|

Peak and integral seismic parameters of L’Aquila 2009 ground motions: observed versus code provision values

Abstract: The M w 6.3 L'Aquila earthquake of April 6, 2009 hit a wide area of the Abruzzo region (Central Italy). The epicentre of the main shock was very close to the urban centre of L'Aquila, the regional capital, with an epicentral distance less than 10 km. It was the strongest earthquake ever recorded in Italy which has provided ground motion recordings from accelerometric stations located in close proximity to the epicentre. Because of this, several remarkable results can be achieved by analysing the strong motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The main information about the selected events is reported in Table 4. According to the spectral analyses shown in the previous sections, we rotated the accelerometric time series in the horizontal plane to obtain the maximum PGA In order to synthesize the results, we report only the parameters recorded along the direction for which the I H is maximum, being I H a parameter better correlated to the energy content of an earthquake rather than PGA to analyze the response of soils and buildings (see e.g., Masi et al 2010). It is worth noting that while the maximum PGA value was recorded at AQV during the mainshock, the M = 5.6 aftershock recorded at MI05 has a PGA larger than the mainshock at the remaining RAN stations.…”
Section: Short Scale Variation Using S-transform Analysismentioning
confidence: 99%
“…The main information about the selected events is reported in Table 4. According to the spectral analyses shown in the previous sections, we rotated the accelerometric time series in the horizontal plane to obtain the maximum PGA In order to synthesize the results, we report only the parameters recorded along the direction for which the I H is maximum, being I H a parameter better correlated to the energy content of an earthquake rather than PGA to analyze the response of soils and buildings (see e.g., Masi et al 2010). It is worth noting that while the maximum PGA value was recorded at AQV during the mainshock, the M = 5.6 aftershock recorded at MI05 has a PGA larger than the mainshock at the remaining RAN stations.…”
Section: Short Scale Variation Using S-transform Analysismentioning
confidence: 99%
“…For l'Aquila event, the difference between the observed recordings and code provision was mainly due to the choice of parameters used rather than in a bias in base hazard estimates or insufficient description of site effects . After correcting for soil class according with Vs30, Masi et al (2011) showed that Housner Intensity provided much better results than PGA (Fig. 5.6), and was well correlated with site seismic hazard obtained from the long series of macroseismic data available.…”
Section: Comparison Between Code Spectra and Observed Strong Motionmentioning
confidence: 70%
“…For validation or confirmation of PSHA using observed ground-motion records, a control period of consecutive observations is necessary (e.g., Albarello and D'Amico, 2008;Beauval et al, 2008;Miyazawa and Mori, 2009;Stirling and Gerstenberger, 2010;Mezcua et al, 2013; see also a review in Stein et al, 2012, anddiscussion in Iervolino, 2013). However, the direct comparison of ground-motion records obtained during a single earthquake with the probabilistic seismic hazard model allows analyzing the consistency of the model and the observations available (e.g., Crowley et al, 2010;Masi et al, 2011;Meletti et al, 2012;Sokolov et al, 2004). The comparison may result not only in compilation of new hazard maps and consequently in new seismic Fig.…”
Section: Discussionmentioning
confidence: 99%